Effect of Acellular Amnion With Increased TGF-β and bFGF Levels on the Biological Behavior of Tenocytes - Sang, Rongli; Liu, Yuanyuan; Kong, Lingyu; Qian, Ligang; Liu, Chunjie (Frontiers in Bioengineering and Biotechnology, 2020)
The human amniotic membrane has been a subject for clinical and basic research for nearly 100 years,but weak rejection has been reported. The purpose of this research is to remove the cellular components of the amnion for eliminating its immune-inducing activity to the utmost extent. The amniotic membrane treated by acid removed the epithelial cell, fibroblast, and sponge layers and retained only the basal and dense layers. In vitro, biological effects of the new material on tenocytes were evaluated. The levels of transforming growth factor (TGF-β1), fibroblast growth factor (bFGF) proteins were measured. In vivo,the tendon injury model of chickens was constructed to observe effects on tendon adhesion and healing. The acellular amniotic membrane effectively removed the cell components of the amnion while retaining the fibrous reticular structure.Abundant collagen fibers enhanced the tensile strength of amnion, and a 3D porous structure provided enough 3D space structure for tenocyte growth. In vitro, acellular amnion resulted in the fast proliferation trend for tenocytes with relatively static properties by releasing TGF-β1 and bFGF. In vivo, the experiment revealed the mechanism of acellular amnion in promoting endogenous healing and barrier exogenous healing by evaluating tendon adhesion, biomechanical testing, and labeling fibroblasts/tendon cells and monocytes/macrophages with vimentin and CD68. The acellular amnion promotes endogenous healing and barrier exogenous healing by releasing the growth factors such as TGF-β1 and bFGF, thereby providing a new direction for the prevention and treatment of tendon adhesion.